Pengaruh Kompensasi, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan ( Studi Kasus Pada UD. Permata Beton Desa Sugihan, Kampak Trenggalek Jawa Timur) - Pramudita, Sekar Arum; Rachma, N; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyze and determine the Effect of Compensation, Work Discipline, and Work Environment on Employee Performance. This study uses Explanatory Research with a quantitative approach. Sampling was carried out on all employees of UD. Permata Beton using a saturated sampling technique. Because the population in this study was 100 people, the entire population will be counted as a sample. This research method uses multiple linear regression analysis with SPSS analysis tools. Hypothesis testing uses the t test and F test. The results of this study indicate that Compensation, Work Discipline, and Work Environment have a significant effect simultaneously on Employee Performance. The variables Compensation, Work Discipline, and Work Environment have a significant partial effect on Employee Performance. Keywords: Compensation, Work Discipline, Work Environment and Employee Performance